Penentuan Pola Tanam Padi dan Jagung Berbasis Neraca Air di Kecamatan Lewa Kabupaten Sumba Timur - Yonce Melyanus Killa; Bistok Hasiholan Simanjuntak; Nugraheni Widyawati (agriTECH, 2018)
Lewa is one of districts in East Sumba Regency, Nusa Tenggara Timur (NTT) Province. It is characterized by dry land, its agriculture depends on rain. The main commodities are Oryza sativa and Zeamays. Due to lack of water, the cropping pattern design is vital. One of methods for designing crroping pattern is water balance analysis. The aim of this study was to understand water balance status and to decide the cropping pattern based of paddy and corn farming in Lewa District. The NRCS Java Newhall Simulation Model (jNSM) was adopted for water balance modeling. The water balance status then was mapped by using the Arc view software for showing total water availability in Lewa district. There were two zones: I (water availability 413 mm/year) and II (water availability: 868 mm/year). Based on the water availability, the zone I could be designed one period a year in rainy season (December-April) with cropping option paddy or corn. While zone II could be planted two times with cropping option corn-paddy or corn-corn.